β-D-Mannuronic Acid (M2000) as a Landmark in Pharmacology - Gaafar, Nada A.G.; Razavi, Alireza; Mirshafiey, Abbas (Current Drug Discovery Technologies, 2021)
Objectives: The goal of this article is to retrace the studies of β-D-Mannuronic Acid (M2000) as a new immunosuppressive drug with non-steroidal anti-inflammatory drugs (NSAIDs) property in miscellaneous aspects including in vitro, in vivo examinations, clinical trials and related to clinical trials studies. Our goal is to compare the effect of this drug with other similar drugs through varied researches and to follow tolerability, biocompatibility, potency, safety, and efficacy of this medication in different studies, as well as to evaluate its therapeutic effectiveness in various diseases. Materials and Methods: Different methods were applied in the studies of β-D-Mannuronic Acid under in vitro, in vivo examinations, and clinical trials phase I, II and III and related investigations to these clinical trials using different techniques showing the efficacy of this medication in the treatment of various diseases. Results: The administration of β-D-Mannuronic Acid showed the greatest tolerability and biocompatibility compared to diclofenac, piroxicam, and dexamethasone without or very low side effects. The drug has shown a punchy effect on many molecules which participate either in physiologic or in pathogenic activities in animal models and human. This new drug not only revealed the anti-inflammatory and immunosuppressive properties but also based on the results of various investigations, β-D-Mannuronic Acid showed the antidiabetic, cardioprotective and anti-tumoral effects. Conclusion: β-D-Mannuronic Acid (M2000) as a novel immunosuppressive drug with NSAID properties along with antidiabetic, cardioprotective and anti-tumoral efficacy showed great tolerability and safety profile. In addition, it has no or mild adverse events compared with many other medicines, therefore this medicament could be considered as a landmark in pharmacology and represent turn point in the treatment of different diseases based on the experimental and in vitro studies explained and clinical and related studies proved.
Keywords: CD147